(untitled) (Revista Brasileira Multidisciplinar, 2020)
The management of construction and demolition waste (C&D Waste) is considered a set of practices of great importance to the environment, either by mitigating the environmental impact generated by the sector, or by adopting more effective solutions at the construction site, transportation, disposal or adequate disposal of waste. The goal of this research aimed at a systemic analysis of the agents involved in the management of construction waste in the city of São José do Rio Preto - SP, based on existing laws and regulations, at the federal, state or municipal field level, showing the experiences, applications and results obtained by the agents involved. Within this field, have been realized a historical research of the management of construction and demolition waste, since the end of the 90’s to the present days through three steps – Diagnosis of practices that rules the management of wastes of the constructions; Preparation and application of field research instrument; Data analysis. Based by the results obtained in this study, it was possible to verify that the city had a gradual evolution in the management of C&D Waste, align with CONAMA Resolution no. 307/2002 and National Policy on Solid Waste 2010.